From Old To New: An Analysis of Changes Between The Old and New Regime of Indonesian Investment Treaties - Mohamad Rafi Andiansyah (Jurnal sosial dan sains, 2022)
International Investment Law as a system relies heavily on the treaties applicable on a case-by-case basis. Most often these treaties are Bilateral Investment Treaties, treaties negotiated between States which offer to promote and protect investment in the two States Party. These treaties are responsible for promoting and protecting billions of dollars’ worth of investments and as such when a country as economically involved in a large region as Indonesia discontinues its existing BITs in hopes of renegotiating a “better” treaty, the situation warrants scrutiny. In 2014, the Government of Indonesia chose to terminate many of the existing BITs, and in 2018, the first of the wave of renegotiated BITs have appeared in the form of the 2018 Indonesia-Singapore BIT. The differences between the old and new BIT must be properly analyzed in order to approximate what impact these new BITs could have on the investment regime in Indonesia.